Blockchain single and interval valued neutrosophic graphs - D., Nagarajan; M., Lathamaheswari; S., Broumi; J., Kavikumar (University of New Mexico, 2019)
Blockchain Technology (BCT) is a growing and reliable technology in various fields such as developing business deals, economic environments, social and politics as well. Without having a trusted central party this technology, gives the guarantee for safe and reliable transactions using Bitcoin or Ethereum. In this paper BCT has been considered using Bitcoins. Also Blockchain Single and Interval Valued Neutrosophic Graphs have been proposed and applied in transaction of Bitcoins. Also degree, total degree, minimum and maximum degree have been found for the proposed graphs. Further, comparative analysis is done with advantages and limitations of different types of Blockchain graphs.